Growth and optimization of III-V semiconductor solar cell structures. - Lim, Kuo Hou. (2011)
In this thesis, MBE and micro fabrication processes are used to fabricate 1×1cm^2 single junction homoface GaAs thin film solar cells. Solar spectrum is used to explain and relate it with the material band gap. Photon energy that is equal or greater than this band gap is then excite an electron to conduction band which lead to photocurrent generation. Solid state theory of pn junction is described to explain the physics of photovoltaic. Detail balance principle is invoked to explain the theoretical development of maximum conversion limit. Literature review involved solar cell device makeup such as thickness, dopant concentration, surface recombination etc are investigated to obtain optimized efficiency. The experimental methods and setup is described to give an overview of the fabrication processes involved. Solar simulator and electrochemical workbench are used to conduct IV characteristic measurement. It is found that a MBE grown 1×1cm2 solar cells under 1 sun illumination at AM1.5 G is able to achieve maximum conversion efficiency closed to 16% with MgF2/ZnS double layers anti reflective coating. This finding is also verified using Silvaco Atlas Software Simulation with similar device makeup and obtained efficiency of about 23%.